Efeito de plantas de cobertura cultivadas no inverno nas propriedades físicas do solo e na produtividade de soja e milho em sucessão - Mottin, Marcos Cesar (2016)
The agricultural production systems have as a fundamental component soil. inadequate cultural practices associated with monoculture has caused soil degradation, natural resources and the productivity of planted crops. This study aimed to evaluate the productivity of biomass cover crops in autumn-winter (Poaceae and Fabaceae), and its effects on soil physical properties at different depths and; Evaluate the productivity of corn and soybean in succession to cover crops (Poaceae and Fabaceae) grown in autumn-winter. The experimental design was randomized blocks with split plots with six replications. The plots consisted of four cover crops in autumn-winter; two Poaceae (black oats and pasture) and two Fabaceae (pea forage and white lupine), and the trade of summer crops (corn and soybeans) grown in succession on these different biomasses. The subplots were different depths reviews (0 - 0.05, 0.05 to 0.10 and 0.10 to 0.15 m). The factors evaluated in this study were: dry matter productivity; soil surface coverage ratio; macroporosity, microporosity, total porosity; bulk density; soil penetration resistance and parameters of production and productivity of commercial summer crops corn and soybean. The plants of the family Poaceae had lower dry mass productivity, however, had higher soil surface coverage ratio and macroporosity. The cover crops cultivation in autumn-winter, promoted to the soil in depth from 0 to 0.05 m, higher macroporosity and total porosity, and lower density. The resistance to penetration depth 0.05 to 0.20 m was smaller in area cultivated with plants Poaceae family. Growing Family Poaceae cover crops (black oats and pasture) and Fabaceae (pea forage and white lupine) in autumn-winter, did not influence the productivity of corn and soybean grown in succession